Cooperative Interplay Between PGPR and Trichoderma longibrachiatum Reprograms the Rhizosphere Microecology for Improved Saline Alkaline Stress Resilience in Rice Seedlings - Junjie Song; Xueting Guan; Lili Chen; Zhouqing Han; Haojun Cui; Shurong Ma (Microorganisms, 2025)
Soil salinization has become a major obstacle to global agricultural sustainability. While microbial inoculants show promise for remediation, the functional coordination between Trichoderma and PGPR in saline alkali rhizospheres requires systematic investigation. Pot studies demonstrated that while individual inoculations of Trichoderma longibrachiatum (M) or Bacillus aryabhattai (A2) moderately improved rice growth and soil properties, their co-inoculation (A2 + M) synergistically enhanced stress tolerance and nutrient availability—increasing available nitrogen (AN +28.02%), phosphorus (AP +11.55%), and potassium (AK +8.26%) more than either strain alone, while more effectively mitigating salinity (EC −5.54%) and alkalinity (pH −0.13 units). High-throughput sequencing further revealed that the A2 + M treatment reshaped the rhizosphere microbiome, uniquely enriching beneficial taxa (e.g., Actinomycetota [+9.68%], Ascomycota [+50.58%], Chytridiomycota [+152.43%]), and plant-growth-promoting genera (e.g., Sphingomonas, Trichoderma), while drastically reducing saline-alkali-adapted Basidiomycota (−87.96%). Further analysis identified soil organic matter (SOM), AN, and AP as key drivers for the enrichment of Chytridiomycota and Actinomycetota, whereas pH and EC showed positive correlations with Mortierellomycota, Aphelidiomycota, unclassified_k__Fungi, and Basidiomycota. Collectively, the co-inoculation of Trichoderma and PGPR strains enhanced soil microbiome structure and mitigated saline alkali stress in rice seedlings. These findings demonstrate the potential of microbial consortia as an effective bio-strategy for saline alkali soil amelioration.